The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1999 International Symposium on Symbolic and Algebraic Computation 1999
DOI: 10.1145/309831.309947
|View full text |Cite
|
Sign up to set email alerts
|

Specifying implementations

Abstract: III t.his papor t.he aua.lysis of t.lie data struct,ures uwd in 21 software systcn1 for SyIuhOlic Clomput.at,ioI1 in Algrlxdc T0l>010g~, ~IIOWU i1S EAT (Ejfedi~~~ Al,~~ehic T'o~o~o~TJ), is undertalwn. Having tho11ght. Of t.lIe rolr: Of fIIIIct.ional IJ~O-grauming in this particular prograru, we 11ilVC come to a generitl rlcfinit,ion of an operation on .\lJstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…5. Moreover, the representation of a set in a computer needs the encoding of the equality of such a set (this was deeply studied in [45]), and setoids can be used with this aim.…”
Section: Defining Algebraic Structures In Acl2 From Scratchmentioning
confidence: 99%
“…5. Moreover, the representation of a set in a computer needs the encoding of the equality of such a set (this was deeply studied in [45]), and setoids can be used with this aim.…”
Section: Defining Algebraic Structures In Acl2 From Scratchmentioning
confidence: 99%
“…In particular, first we studied one of the most important aspects of EAT, that is, its data structures. In that study [21,22] we found that there are two different layers of data structures in EAT. In the first layer, one finds the usual data structures.…”
mentioning
confidence: 97%
“…Then, a Σ imp -algebra defines a family of Σ-algebras (the carrier set for the distinguished sort acts as an index for this family). Besides, working with implementations in [21] we were able to prove that EAT (second-layer) data structures are as general as possible, in the sense that they are ingredients of final objects in certain categories of ADT implementations. Later on, led by this characterization of EAT data structures, in [22] we reinterpreted our results in terms of hidden algebras [15] and coalgebras [27], technologies that have been presented in the literature as related to the object-oriented paradigm [14,18,27].…”
mentioning
confidence: 98%
See 2 more Smart Citations